2018
DOI: 10.1016/j.ygyno.2018.04.570
|View full text |Cite
|
Sign up to set email alerts
|

Stromal invasion pattern identifies patients at lowest risk of lymph node metastasis in HPV-associated endocervical adenocarcinomas, but is irrelevant in adenocarcinomas unassociated with HPV

Abstract: Application of the Silva system is only relevant in HPVA cervical adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 16 publications
4
33
0
6
Order By: Relevance
“…Consistent with our results, a recent study showed that Pattern Classification is only suitable for HPVrelated ADCs. 21 Studies have provided increasing evidence that the predictive index of Pattern Classification correlates with LVSI, status of LN metastasis, tumour size, FIGO stage, tumour thickness or DOI, perineural invasion, and recurrence-free survival. 16,17 Invasion pattern as well as tumour size, DOI, LVSI, and LN metastasis have been reported to be independent predictors of recurrence-free and disease-specific survival in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, a recent study showed that Pattern Classification is only suitable for HPVrelated ADCs. 21 Studies have provided increasing evidence that the predictive index of Pattern Classification correlates with LVSI, status of LN metastasis, tumour size, FIGO stage, tumour thickness or DOI, perineural invasion, and recurrence-free survival. 16,17 Invasion pattern as well as tumour size, DOI, LVSI, and LN metastasis have been reported to be independent predictors of recurrence-free and disease-specific survival in a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Invasion pattern as well as tumour size, DOI, LVSI, and LN metastasis have been reported to be independent predictors of recurrence-free and disease-specific survival in a multivariate analysis. 21 However, whether LN metastasis or LVSI is an independent predictor for overall survival remains controversial. Roma et al reported that LVSI is not an independent predictor of outcome if LN status is considered.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasised that pattern classification applies only to HPV‐associated adenocarcinoma and not any of the non‐HPV subtypes. Two independent studies have shown that all non‐HPV‐associated adenocarcinomas were categorised as pattern C …”
Section: Classification Of Endocervical Adenocarcinomamentioning
confidence: 99%
“…The validity of this new classi cation is supported by HPV status and, at present, by limited clinical data (8,9). In the present study, the following HPV tests were used: PCR, genotype, RNAscope, and immunochemistry (IHC) against p16 protein.…”
Section: Introductionmentioning
confidence: 90%